HIV-Exposed Uninfected Infants Have Increased Regulatory T Cells That Correlate With Decreased T Cell Function - Jalbert, Emilie; Williamson, Kayla M.; Kroehl, Miranda E.; Johnson, Michael J.; Cutland, Clare; Madhi, Shabir A.; Nunes, Marta C.; Weinberg, Adriana (Frontiers in Immunology, 2019)
Background HIV-exposed uninfected infants (HEU) are at higher risk of severe infections, hospitalizations and death compared with HIV-unexposed uninfected infants (HUU), but the immune deficit underlying it is not known. To address this gap, we investigated T cell functionality and its relationship to phenotypic profiles of T cells and antigen presenting cells (APC) in HEU and HUU. Methods Blood mononuclear cells from 55 HEU and 16 HUU were stimulated with Staphylococcal Enterotoxin B (SEB) or mock for 72 h, and tested by flow cytometry for proliferation and expression of Th1, Th2 and regulatory (Treg) markers. In parallel, cells were phenotypically assessed for differentiation profiles of Treg, conventional T cell (Tconv) and APC in unstimulated cells. Results HEU had lower CD4+ functional responses to SEB/mock and similar CD8+ responses compared with HUU. In the phenotypic T cell panel, HEU showed higher proportions of CD4+ and CD8+ Treg expressing IL10, FOXP3 and CD25; higher effector Tconv and Treg; and lower naïve and CD4+TGF+ Treg compared with HUU. In the phenotypic APC panel, HEU showed higher proportions of CD1c+ cDC2, CD123+ pDC, CD16+ inflammatory monocytes and cDC and higher expression of CD103 on CD1c-CD123-CD16- cDC1 compared with HUU. Regression analyses adjusted for HIV exposure and multiple comparisons showed that higher CD8+IL10+ and CD8+FOXP3+ Treg in unstimulated cells were associated with lower CD8+ T cell functional responses to SEB/mock. Functionality was not affected by Tconv differentiation, but higher APC activation in aggregate was associated with higher CD8+IL10+ Treg responses to SEB. Conclusions T cell functionality was decreased in HEU compared with HUU. High CD8+ Treg proportions were the most important predictors of decreased T cell functionality.